Study of a Weather Prediction System Based on Fuzzy Logic Using Mamdani and Sugeno Methods - Setyanugraha, Noval; Al Aziz, Sofyan; Harmoko, Iis Widya; Fianti, Fianti (Universitas Negeri Semarang, 2022)
Weather is a very important factor in supporting various human activities. However, weather is a natural event that keeps on changing due to various air conditions that affect it. One way to anticipate weather changes that may occur early is to create a system that can predict weather changes. Fuzzy logic is one of the methods that can be used in system prediction to find out the cause at a certain time and place. In this system, two fuzzy logic methods were used, they are the Mamdani and Sugeno methods, with three supporting criteria, including air temperature, humidity, and air pressure. In this research, data levers were carried out in June 2022 and resulted in a percentage accuracy of 73.34% for the Mamdani method and 70% for the Sugeno method.